Comparison of advanced and intermediate 200-m backstroke swimmers' dominant and non-dominant shoulder entry angles across various swimming speeds - Andrews, C.; Bakewell, J.; Scurr, J. C. (Journal of Sports Sciences, 2011)
During backstroke, an optimum shoulder entry angle of 180° has been anecdotally suggested; however, this has yet to be investigated biomechanically. The aim of this study was to quantify shoulder entry angles for advanced and intermediate backstroke swimmers. Six advanced (season's best <150 s) and six intermediate (season's best >160 s) 200-m backstroke swimmers had markers applied to the medial humeral epicondyles and glenoid cavities. Following a familarization period, participants completed backstroke swimming trials (90 s each) in a swimming flume at 50%, 60%, 70%, and 80% of their season's best 200-m velocity. A camera positioned above the flume recorded frontal plane motion, which was digitized and analysed in Simi Motion Systems. The mean peak angle between the upper arm and the line of progression was established in ten strokes for each participant. The results showed backstroke shoulder entry angles for advanced swimmers (170°) were significantly closer to the suggested optimum 180° compared with those of intermediate swimmers (161°). The non-dominant arm displayed values closer to the optimum (171°), while swimming speed had no effect on backstroke shoulder entry angle. In conclusion, backstroke shoulder entry angle may help discriminate between advanced and intermediate backstroke swimmers and may be influenced by laterality dominance, being independent of swimming speed.